2019
DOI: 10.1111/1750-3841.14668
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Mechanism of Catechin, Resveratrol, Butylated Hydroxylanisole, and Tert‐Butylhydroquinone on Carboxymethyl 1,2‐Dipalmitoyl‐sn‐Glycero‐3‐Phosphatidylethanolamine Formation

Abstract: It is important to inhibit the food‐derived, potentially hazardous chemical glycated lipids by natural products. A model system was established and the products are identified to study the inhibitory mechanism of four types of catechin, resveratrol (RES), and the synthetic antioxidants butylated hydroxylanisole (BHA) and tert‐butylhydroquinone (TBHQ) on the formation of carboxymethyl 1,2‐dipalmitoyl‐sn‐glycero‐3‐phosphatidylethanolamine (CM‐DPPE) by determining hydroxyl radical (OH·), Amadori‐1,2‐dipalmitoyl‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The TBHQ cannot reduce acrylamide in model asparagine-glucose system; however, interactions between the oxidized products from TBHQ (e.g., quinones) with asparagine affect acrylamide formation [57] . Han, Lin [58] found that TBHQ could inhibit the formation of Amadori compounds via removing OH° or trapping glyoxal. Indeed, TBHQ is a chain-breaking as radical chain‐breaking antioxidant.…”
Section: Tert-butylhydroquinone Reaction In Foodsmentioning
confidence: 99%
“…The TBHQ cannot reduce acrylamide in model asparagine-glucose system; however, interactions between the oxidized products from TBHQ (e.g., quinones) with asparagine affect acrylamide formation [57] . Han, Lin [58] found that TBHQ could inhibit the formation of Amadori compounds via removing OH° or trapping glyoxal. Indeed, TBHQ is a chain-breaking as radical chain‐breaking antioxidant.…”
Section: Tert-butylhydroquinone Reaction In Foodsmentioning
confidence: 99%